HigB1 Toxin in Mycobacterium tuberculosis Is Upregulated During Stress and Required to Establish Infection in Guinea Pigs - Sharma, Arun; Sagar, Kalpana; Chauhan, Neeraj Kumar; Venkataraman, Balaji; Gupta, Nidhi; Gosain, Tannu Priya; Bhalla, Nikhil; Singh, Ramandeep; Gupta, Amita (Frontiers in Microbiology, 2021)
The extraordinary expansion of Toxin Antitoxin (TA) modules in the genome of Mycobacterium tuberculosis has received significant attention over the last few decades. The cumulative evidence suggests that TA systems are activated in response to stress conditions and are essential for M. tuberculosis pathogenesis. In M. tuberculosis, Rv1954A-Rv1957 constitutes the only tripartite TAC (Toxin Antitoxin Chaperone) module. In this locus, Rv1955 (HigB1) encodes for the toxin and Rv1956 (HigA1) encodes for antitoxin. Rv1957 encodes for a SecB-like chaperone that regulates HigBA1 toxin-antitoxin system by preventing HigA1 degradation. Here, we have investigated the physiological role of HigB1 toxin in stress adaptation and pathogenesis of Mycobacterium tuberculosis. qPCR studies revealed that higBA1 is upregulated in nutrient limiting conditions and upon exposure to levofloxacin. We also show that the promoter activity of higBA1 locus in M. tuberculosis is (p)ppGpp dependent. We observed that HigB1 locus is non – essential for M. tuberculosis growth under different stress conditions in vitro. However, guinea pigs infected with higB1 deletion strain exhibited significantly reduced bacterial loads and pathological damage in comparison to the animals infected with the parental strain. Transcriptome analysis suggested that deletion of higB1 reduced the expression of genes involved in virulence, detoxification and adaptation. The present study describes the role of higB1 toxin in M. tuberculosis physiology and highlights the importance of higB1 locus during infection in host tissues.